Regulation of tumor growth by leukocyte-specific protein 1 in T cells - Riri Kwon; Bong-Ki Hong; Kang-Gu Lee; Eunbyeol Choi; Laurent Sabbagh; Chul-Soo Cho; Naeun Lee; Wan-Uk Kim (Journal for ImmunoTherapy of Cancer)
Background Clinical efficacy of T cell-based cancer immunotherapy is limited by the lack of T cell infiltration in the tumor mass, especially in solid tumors. Our group demonstrated previously that leukocyte-specific protein 1 (LSP1), an intracellular signal regulator, negatively regulates T cell infiltration in inflamed tissues.Methods To determine the immuno-regulatory effects of LSP1 in T cells on tumor progression, we investigated the growth of B16 melanoma in Lsp1 knockout (KO) mice and T cell-specific Lsp1 transgenic (Tg) mice. The immune cell subpopulation infiltrated into the tumor mass as well as the expression of interferon-gamma (IFN-γ) and tumor necrosis factor-alpha (TNF-α) in T cells was assessed by flow cytometry and/or immunohistochemistry. Chemotactic migration was assayed with Lsp1 KO and Lsp1 Tg T cells. Adoptive transfer of Lsp1 KO or Lsp1 Tg T cells was performed in B16 melanoma-challenged Rag1 KO mice.Results Lsp1 KO mice showed decreased growth of B16 melanoma and increased infiltration of T cells in the tumor mass, which were completely reversed in T cell-specific Lsp1 Tg mice. Lsp1 KO CD8+ T cells also exhibited elevated migratory capacity in response to CXCL9 and CXCL10, whereas Lsp1 Tg CD8+ T cells did the opposite. LSP1 expression was increased in tumor-infiltrating T cells and could be induced by T cell receptor activation. Intriguingly, gene expression profiling of Lsp1 KO T cells suggested enhanced cytotoxicity. Indeed, expression of IFN-γ and TNF-α was increased in tumor-infiltrating CD4+ and CD8+ T cells of Lsp1 KO mice, while it was markedly reduced in those of Lsp1 Tg mice. Adoptive transfer of Lsp1 KO T cells to Rag1 KO mice was more effective in suppressing melanoma growth than transfer of Lsp1 Tg T cells. Of note, when treated with antiprogrammed cell death protein 1 (PD-1) antibody, inhibition of melanoma growth was more pronounced in Lsp1 KO mice than in Lsp1-sufficient mice, suggesting that Lsp1 depletion additively increases the antitumor effects of anti-PD-1 antibody.Conclusions LSP1 in T cells regulates the growth of B16 melanoma in mice, possibly by affecting migration and infiltration of T cells into the tumor and by modulating production of antitumor effector cytokines by CD8+ T cells. These findings provide evidence that LSP1 can be a target to improve the efficacy of T cell-based immunotherapy.